Preclinical evaluation of a novel thermally sensitive co-polymer (LiftUp) for endoscopic resection. Issue 5 (3rd September 2019) - Wedi, Edris; Ho, Chi-Nghia; Conrad, Gabor; Weiland, Timo; Freidinger, Stefanie; Wehrmann, Manfred; Meining, Alexander; Ellenrieder, Volker; Gottwald, Thomas; Schurr, Marc Oliver; Hochberger, Juergen
Abstract: Introduction: Endoscopic resection techniques can successfully resect large lesions either in "en bloc" fashion or in "piece-meal" technique by using a submucosal injection solution. The aim of this study was to evaluate the safety of a novel injectable, containing thermally sensitive co-polymer from ethylenoxide and propylenoxide (LiftUp) used as submucosal injection solution. Material and methods: We conducted an in vivo animal trial in the porcine model to evaluate the LiftUp gel in a preclinical setting and to study the effectiveness of mucosal lifting and the safety of the new injectable. In seven animals a total of 63 injections and endoscopic resections were carried out in different anatomical locations (esophagus, stomach and rectum). The resection sites were controlled endoscopically one and four weeks after resection and a histopathological evaluation of the resection sites was performed after four weeks. Results: The application of LiftUp was safe and there were no negative effects on wound healing after injection and resection. A major procedural complication rate (defined as perforation and major haemorrhage) of 3.2% was registered, which undercuts the anticipated mean complication rate of 4–8%. Furthermore, there was no necessity of reinjection after the initial submucosal injection in 90.5% and no procedural complications in 98.8%. The histopathological examination of the tissue samples indicated normal wound healing with granulation tissue and epithelialisation. Conclusion: The use of LiftUp as submucosal injection solution was feasible for different endoscopic resection techniques, with high and long-lasting elevation and fewer procedural adverse events than expected at trial planning. The new injectable is a practical advancement over the current state-of-the-art of submucosal injection and could fasten up the resection procedure and make endoscopic 'en bloc' resection safer.